Ecological wisdom in the legend of Otak Aiq Tojang: An ecocritical analysis - Hilmi, Hubbi Saufan; Andayani, Andayani; Wardani, Nugraheni Eko (Universitas Syiah Kuala, 2024)
This study examines the Legend of Otak Aiq Tojang to explore ecological wisdom and spirituality within the Sasak people. Otak Aiq Tojang is a spring sacred to the Sasak people in Lendang Nangka village. This study used a literary ecocriticism approach with data collection techniques in the form of observation and interviews. Interviews were conducted with five informants representing predetermined social layers in the community using purposive sampling. The analysis reveals that the legend has profound significance in Sasaks life, symbolizing a harmonious balance between humans and nature. The connection between ecological policy and sustainability is underscored by the legend of Dewi Anjani, a purported mythological being, and Betere Indra Guru Saktis arrival and subsequent discovery of the spring. These tales have an impact on religious observances, including Begawe Beleq and Maulid Adat, which commemorate Prophet Muhammads birth. These legends serve not only as historical narratives but also as sources of spiritual and ecological insights. The water deemed auspicious by Otak Aiq Tojang symbolizes sustainability, reflecting the communitys holistic perspective on the environment. Prohibitions of indiscriminate entry and specific food offerings during rituals signify a dedicated preservation effort, illustrating the interconnectedness of cultural norms and ecosystem maintenance. This study enhances our understanding of Sasaks ecological wisdom, particularly within the context of the Otak Aiq Tojang legend. The implications extend to a deeper comprehension of the interplay between myths, religious rituals, and nature conservation in local cultural settings, thus providing a basis for future research in this domain.